Linking Inclusive Leadership, Workplace Spirituality, and Innovative Work Behaviour to Job Performance: An Empirical Study in Public Sector - Aldita Kusuma Rahmi; Putri Mega Desiana (Journal of Theoretical and Applied Management (Jurnal Manajemen Teori dan Terapan), 2023)
Objective: This study investigates the relationship between inclusive leadership and workplace spirituality by the mediating role of innovative work behaviour on the job performance of public service employees. Design/Methods/Approach: This study involved 904 public sector employees. Data were collected via an online survey using a 7-point Likert scale. The sampling method employed was non-probability and purposive sampling based on predefined criteria. The collected data was analyzed using Lisrel 8.80 through Structural Equation Modelling (SEM) weighted least squares (WLS) estimation. Findings: The results indicate that inclusive leadership and workplace spirituality positively and significantly impact innovative work behaviour and job performance. Additionally, innovative work behaviour has a positive and significant impact on job performance. Meanwhile, innovative work behaviour acted as a partial mediator in the relationship between inclusive leadership and job performance and workplace spirituality and job performance. Originality/Value: Research in public organizations has predominantly treated innovative work behaviour as a dependent variable influenced by organizational environmental factors. There has been a notable absence of studies examining innovative work behaviour as an independent variable within the context of public organizations. Concurrently, despite evidence in several studies indicating the impact of a spiritual climate on innovative work behaviour, such an investigation remains unexplored within the realm of public organizations. Practical/Policy implication: The public sector is advised to foster a climate conducive to workplace spirituality by encouraging the uniqueness and capabilities of employees to nurture a sense of meaning in their work. Moreover, public organizations should nurture leaders with inclusive leadership abilities, such as openness, accessibility, and availability, to stimulate employee innovation.